Development of research on HIV-associated neurocognitive disorder and emerging trends: a visualization analysis via CiteSpace - Zhou, Tingting; Chen, Xuannan; Lai, Yu (Frontiers in Immunology, 2025)
BackgroundIn the combination antiretroviral therapy era, HIV-associated neurocognitive disorder (HAND) is still widespread among HIV-infected individuals. However, there is no effective treatment for HAND, and the exact pathogenic mechanism of HAND remains unknown. This paper aims to provide a reference for further exploration in the field of HAND research.MethodsWe used CiteSpace software to collect 3057 articles related to HAND in the Web of Science Core Collection for comprehensive analysis. Betweenness centrality, count, and burst values were used as indicators in the visualization analysis, aiming to predict future new directions and cutting-edge trends.ResultsThe last decade has been the peak period of HAND research, with the most prominent contributions by authors, countries, and institutions being Grant, Igor (135), the USA (2211), and the University of California System (758), respectively. The most frequently cited article is “HIV-associated neurocognitive disorders persist in the area of potent antiretroviral therapy: CHARTER Study.” The hotspots in this field are “neurocognitive impairment,” “central nervous system,” “cerebrospinal fluid,” “HIV-1 tat,” “SIV,” “inflammation,” “infection,” and “pathogenesis.” The current research direction of HAND is focused on exploring the pathogenic mechanism underlying HIV-associated neurocognitive impairment and potential therapeutic targets.ConclusionThis study provides a bibliometric visualization of HAND-related literature to gain insight into the development and frontiers of this research field. The study also provides scholars with detailed references and identifies future research directions to better promote the development of this field of research.